2010
DOI: 10.1103/physreva.82.023808
|View full text |Cite
|
Sign up to set email alerts
|

From a discrete to a continuous model for interpulse interference with a frequency-comb laser

Abstract: We have investigated correlation patterns generated by a frequency-comb laser in a dispersive unbalanced Michelson interferometer and apply the developed formalism to the case of distance metrology. Due to group velocity dispersion, the position of the brightest fringe of the correlation pattern, which is used for distance determination, cannot be derived by simply using the definition of group refractive index of the dispersive medium. It is shown that the discrete spectrum of the optical frequency comb gives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…Also, the position of the coherence maximum or the brightest fringe will vary as a function of the delay distance. We have shown that [16], even if the medium is homogeneous, the position of the maximum coherence varies non-linearly for short delay distances and linearly for larger delay. In addition, our simulations also show that the correlation patterns are non-linearly broadened at short delay distances and that linear broadening replaces the non-linear broadening at larger distances.…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…Also, the position of the coherence maximum or the brightest fringe will vary as a function of the delay distance. We have shown that [16], even if the medium is homogeneous, the position of the maximum coherence varies non-linearly for short delay distances and linearly for larger delay. In addition, our simulations also show that the correlation patterns are non-linearly broadened at short delay distances and that linear broadening replaces the non-linear broadening at larger distances.…”
Section: Introductionmentioning
confidence: 87%
“…A detailed description of our work can be found in [16]. The frequency spectrum emitted by a mode-locked laser consists of a comb of regularly spaced frequencies ω m = mω r + ω 0 , m = 0, 1, 2, ... where ω 0 is the common offset frequency and ω r is the repetition frequency f r expressed in angular notation…”
Section: Cross-correlation In Dispersive Mediamentioning
confidence: 99%
See 3 more Smart Citations